2008
DOI: 10.1021/ma702695a
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of an Amphiphilic Rod−Coil−Rod Block Copolymer into Liquid Crystalline, Substrate-Supported Monolayers and Bilayers

Abstract: We report that the amphiphilic rod−coil−rod triblock copolymer with a coil attractive to the substrate surface self-organize into liquid crystalline monolayers or bilayers of a few nanometers thickness on the substrate surface. The copolymer investigated is a triblock copolymer, poly(n-hexyl isocyanate-b-2-vinylpyridine-b-n-hexyl isocyanate) (PHIC-b-P2VP-b-PHIC). Key processes of self-organization in the thin films, such as adsorption, desorption, diffusion, nematic and smectic ordering, and microphase separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…24 For films of rod−coil LC BCPs, anchoring of the LC relative to the substrate can affect the orientation of the lamellar or cylindrical microdomains. 41,42 Apart from experimental investigations of the molecular adsorption of rod−coil BCPs on substrates, 41,43,44 much of the research on thin film self-assembly and directed self-assembly of rod−coil BCPs has been based on simulations 45,46 and experimental investigations of the thin film microdomain ordering and directed self-assembly of rod− coil BCPs remain sparse.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 For films of rod−coil LC BCPs, anchoring of the LC relative to the substrate can affect the orientation of the lamellar or cylindrical microdomains. 41,42 Apart from experimental investigations of the molecular adsorption of rod−coil BCPs on substrates, 41,43,44 much of the research on thin film self-assembly and directed self-assembly of rod−coil BCPs has been based on simulations 45,46 and experimental investigations of the thin film microdomain ordering and directed self-assembly of rod− coil BCPs remain sparse.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polymers in the L J,2 structure may adopt a bridge conformation 41 or a loop conformation. 27 We find about 16% of polymers adopt the bridge conformation as that plotted in the inset of Fig. 7(b).…”
Section: Self-assembly Of R 4 C 12 R 4 Copolymers Within Nanoslitsmentioning
confidence: 60%
“…Kim et al observed that PHIC-b-P2VP-b-PHIC RCR triblock copolymers self-assembled into liquid crystalline monolayers or bilayers of a few nanometers thickness on the coil-attractive substrate surface. 27 Their results indicated that the self-assembly of the RCR triblock copolymers in thin film can be controlled by adjusting the interactions of every block with the substrate surface, solvents and the amount of deposited copolymers. Similar to RC diblock copolymers, it is difficult to obtain self-assembled equilibrium structures of RCR triblock copolymer films in experiments as well.…”
Section: Introductionmentioning
confidence: 99%
“…Note that holes are formed on the flat region, $6 nm in depth, implying a monolayer deposited on the substrate. 39 In the monolayer, the more hydrophilic P4VP blocks should adhere to the silicon substrate while the PF blocks are exposed to the air. Comparing Fig.…”
Section: Microphase Separation Of Pf-b-p4vpmentioning
confidence: 99%